Simulated Neutrino Signals of Low and Intermediate Energy Neutrinos on Cd Detectors - Sinatkas, J.; Tsakstara, Vaitsa; Kosmas, Odysseas (Frontiers in Physics, 2019)
Neutrino-nucleus reactions cross sections, obtained for neutrino energies in the range ε_ν≤ 100-120 MeV (low- and intermediate-energy range), which refer to promising neutrino detection targets of current terrestrial neutrino experiments, are presented and discussed. At first, we evaluated original cross sections for elastic scattering of neutrinos produced from various astrophysical and laboratory neutrino sources with the most abundant Cd isotopes ^112Cd, ^114Cd and ^116Cd. These isotopes constitute the main material of the COBRA detector aiming to search for neutrinoless double beta decay events and neutrino-nucleus scattering events at the Gran Sasso laboratory (LNGS). The coherent ν-nucleus reaction channel addressed with emphasis here, dominates the neutral current ν-nucleus scattering, events of which have only recently been observed for a first time in the COHERENT experiment at Oak Ridge. Subsequently, simulated ν-signals expected to be recorded at Cd detectors are derived through the application of modern simulation techniques and employment of reliable neutrino distributions of astrophysical ν-sources (as the solar, supernova and Earth neutrinos), as well as laboratory neutrinos (like the reactor neutrinos, the neutrinos produced from pion-muon decay at rest and the β-beam neutrinos produced from the acceleration of radioactive isotopes at storage rings as e.g. at CERN).